Reconstruction and identification of tau lepton decays to hadrons and nu(tau) at CMS - Khachatryan, V. (2016)
This paper describes the algorithms used by the CMS experiment to reconstruct and identify tau -> hadrons + nu(tau) decays during Run 1 of the LHC. The performance of the algorithms is studied in proton-proton collisions recorded at a centre-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 19.7 fb(-1). The algorithms achieve an identification efficiency of 50-60%, with misidentification rates for quark and gluon jets, electrons, and muons between per mille and per cent levels.